Nonprofit fundraising 101 : a practical guide with easy to implement ideas & tips from industry experts - Heyman, Darian Rodriguez, 1974- (Hoboken, New Jersey : Wiley, 2016)
"Nonprofit Fundraising 101 is a practical guide for nonprofit professionals and decision makers that helps them take their cause mobile. Building on the success of the author's previous title, Nonprofit Management 101, Nonprofit Fundraising 101 takes readers deep into the specific applications of mobile technology -- one of the hottest topics for nonprofits. This this new book provides readers with practical tips and tools, as well as expert advice and insights from a variety of well-recognized industry experts, comprehensively addressing all areas a nonprofit can utilize mobile technology. It expertly addresses how to use mobile to build and retain audiences, manage and promote content, recruit and utilize volunteers, fundraise more efficiently and effectively, and monitor organizations' goals and key performance indicators, as well as offers specific mobile tools and applications that will meet each nonprofits needs. Readers of this book get a comprehensive look at a critical and emerging set of tools and practices, all designed to empower and enable them to use mobile technology to run their nonprofits more effectively and efficiently. Also features a toolkit of resources, best practices, and practical tips to establish and maintain a robust mobile presence for their nonprofit. Nonprofit Fundraising 101 addresses the entire spectrum of mobile technology use for nonprofits, including information on topics ranging from organizational effectiveness, audience building and communications strategies, volunteer recruitment and management, as well as an overall guide to existing tools and applications"--
Sponsorship Proposal Template -- ch. 24 Cause Marketing Partnerships / Joe Waters -- Inset: Cause Marketing Proposal Tips -- ch. 25 In-Kind Fundraising and Media Sponsorship / Gayle Samuelson Carpentier -- pt. 7 Unlocking Social Enterprise -- ch. 26 Earned Income Strategies / Rick Aubry -- Social Enterprise Case Study: Grow Dat -- Afterword: Finding Your Path / Premal Shah -- Closing thoughts.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Nonprofit organizations; Fund raising; Organizations, Nonprofit; Fund Raising; Associations sans but lucratif; Collecte de fonds; nonprofit organizations; fund raising; BUSINESS & ECONOMICS -- Nonprofit Organizations & Charities; Fund raising; Nonprofit organizations